Perwujudan Desentralisasi Sebagai Bentuk Akuntabilitas Pemerintah Daerah Kabupaten Cirebon - Arif Rahman; Didin Muhafidin (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
Cirebon Regency is one of the regencies in West Java Province that implemented of decentralization as a form of commitment in carrying out the mandate of the central government and the local government of West Java Province which indicating as one of the regions that contributed to the lack of optimalization of government effectiveness and the human development index in Indonesia. The purpose of this study is to find out more about the realization of decentralization that has been carried out by the Local Government of Cirebon Regency as a form of their accountability in building and prospering public. The method in this study using the method of content analysis with qualitative approach. Overall, the result of this research was the implementation of decentralization in Cirebon Regency has not been fully realized, due to the lack of optimalization in strategic planning through the implementation and controlling; technical problems related to inadequate in supporting facilities and infrastructure, and still not done for adaptability to current and future conditions in realizing sustainable regional development in Cirebon Regency, both in the economic, environmental and social fields.